Guilty acts, guilty minds - Garvey, Stephen P., 1965- (New York, NY : Oxford University Press, 2020)
'You can't be convicted of a crime without a guilty act and a guilty mind.' A lawyer might express the same idea using Latin: 'You can't be convicted of a crime without actus reus and mens rea.' 'Guilty Acts, Guilty Minds' proposes an interpretation of mens rea and actus reus as limits on the authority of a democratic state to ascribe guilt through positive law to those accused of crime.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 11, 2020).
Keywords: Criminal intent -- Philosophy; Criminal justice, Administration of -- United States